Estudio de factibilidad para la implementación de un call center "médico en línea" en la ciudad de Guayaquil - Auria, P. (2009)
The present project treats on a study of feasibility that was realized in certain sector of the city of Guayaquil for the implementation of the DOCTOR'S service IN LINE. The scope of the project is to be announced as a center of medical telephonic consultation, where one of his(her,your) principal aims(lenses) is to avoid of indirect form the poisonings for automedication that they could commit an outrage against the human life, provided that the statistics of the National Institute of Statistics and Censuses (INEC) indicate that 7 of every 10 medicines acquired in drugstores of the city are without any type of medical prescription, only consumed by advice(council) of acquaintances or relatives. It thinks that the implementation of this project would solve in 60 % the current problems, influencing in a positive way for the society, for what on having finished with this one I study certain recommendations appear for the same one.